Probiotics mitigate thermal stress- and pathogen-driven impacts on coral skeleton - Moradi, Mahdi; Magalhaes, Phillipe R.; Peixoto, Raquel S.; Jonck, Cassia C.A.C.; François, Daniel; Bellot, Anna Clara F.; Teixeira, Jonatã B.; Silveira, Carla S.; Duarte, Gustavo; Evangelista, Heitor; Barbosa, Catia F. (Frontiers in Marine Science, 2023)
Threats leading to a reduction in coral populations are apparent worldwide. Several different approaches have been tested to accelerate the adaptation of corals to a changing climate. Here, we evaluated the skeleton structure, crystal habit, and chemical changes of the coral Pocillopora damicornis in response to the pathogen (Vibrio coralliilyticus) and probiotic (Beneficial Microorganisms for Corals, BMCs) inoculation under ambient conditions (26 °C) and thermal stress (30 °C) during a 50-day mesocosm experiment. The skeletons were analyzed using microtomography, energy-dispersive x-ray spectroscopy (EDX/SEM), and densitometry to investigate the skeleto-physico-chemical micro-morphological changes in porosity, median pore-size diameter, crystal habit, Mg/Ca, Sr/Ca, the skeleton mineral density (g/cm2) and skeleton mineral content (g–2). The results indicate considerable changes in the coral skeleton caused by both temperature and microbial inoculation. Most importantly, lower density (to ∼ x̄ 0.5 g/cm2) and higher porosity (up to ∼ x̄ 47%) were correlated with inoculation of V. coralliilyticus and mitigated by probiotics. BMCs also substantially increased calcification, as evidenced by Mg/Ca in the skeleton of thermally stressed corals. At the micron scale, aragonite crystal fibbers precipitated during the experiments showed an acicular habit in thermally stressed and pathogen-inoculated corals kept at 30 °C. In contrast, a spherulitic habit, characteristic of high growth rates, was observed in corals inoculated with both BMCs and V. coralliilyticus. Our findings reveal that pathogen inoculation and thermal stress had notable impacts on coral skeleton properties, including porosity, density, and crystal morphology, in a short period of time, which highlights the potential impacts of shifts in climate warming and environmental quality. Interestingly, BMCs played a role in maintaining the properties of skeleton calcification.